How serve origin-destination and receiver contact point shape reception in elite women`s volleyball - Martínez, E. L.; López-Serrano, C.; Gonzalez, C. H.; Martín, J. H. M. (Journal of Sports Sciences, 2026)
Reception is a critical determinant of success in elite volleyball, yet the combined influence of serve trajectory and contact point remains underexplored, particularly in women`s competitions. This study analysed how the interaction between serve trajectory (origin and destination zones) and the receiver`s contact point affects reception quality in high-level women`s volleyball. It was hypothesised that receptions performed with middleline contact would achieve higher performance than those executed with lateral or low contacts, regardless of serve trajectory. A total of 39,974 receptions from the Olympic Games and Volleyball Nations League (2021 and 2024) were evaluated using descriptive statistics and logistic regression models (multinomial, binomial, and ordinal). The results showed that receptions after serves from zone 6 and made with contact on the centre line achieved significantly higher performance. In contrast, those directed towards zones 5 and 3, especially with low or lateral contacts, performed worse. When we understand how the serve zone, the reception zone and the point of contact with the ball are connected, reception is no longer seen as a mechanical gesture but as a dynamic process where technique and tactics come together. This understanding guides us towards training and strategies more connected to the essence of the game.